2015
DOI: 10.1111/1471-0307.12215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different matrices on probiotic resistance to in vitro simulated gastrointestinal conditions

Abstract: In this study, we evaluated the effect of different matrices (MRS, milk and milk with inulin) on the tolerance of probiotic strains (Lactobacillus acidophilus La-5 and Bifidobacterium animalis subsp. lactis BB-12) to simulated conditions similar to those found in the gastrointestinal tract. Both probiotic strains demonstrated a significantly lower viability after exposure to in vitro gastric and intestinal conditions, and B. animalis subsp. lactis BB-12 showed higher survival during the test compared to L. aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…We also checked for the presence of any plasmid by Qiagen Plasmid Mini Kit (Qiagen, USA). The bile and acid tolerance assay (61–64) autoaggregation(65), cell surface hydrophobicity (66), adhesion to human HT-29 cell line (67, 68),bile-salt hydrolytic (BSH) activity (69), resistance to hydrogen peroxide (70–72) exopolysaccharide production (73), hemolytic activity (74–76), resistance to simulated GIT conditions (7779), serum resistance (80), resistance to Simulated GI Conditions (77, 81, 82) and gluten degradation (83) was carried out as stated.…”
Section: Methodsmentioning
confidence: 99%
“…We also checked for the presence of any plasmid by Qiagen Plasmid Mini Kit (Qiagen, USA). The bile and acid tolerance assay (61–64) autoaggregation(65), cell surface hydrophobicity (66), adhesion to human HT-29 cell line (67, 68),bile-salt hydrolytic (BSH) activity (69), resistance to hydrogen peroxide (70–72) exopolysaccharide production (73), hemolytic activity (74–76), resistance to simulated GIT conditions (7779), serum resistance (80), resistance to Simulated GI Conditions (77, 81, 82) and gluten degradation (83) was carried out as stated.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown previously that food matrix plays a significant role in protecting the probiotic bacteria from gastrointestinal stress (Casarotti et al., 2015). Therefore, pineapple matrix having a dietary fiber‐rich, porous structure acted as a good support to adhere and protect the probiotic bacteria during the simulated gastrointestinal transit (Borges et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Food matrix has also been shown to play significant role in protecting the probiotic species under gastrointestinal stress. The gel forming tendency of prebtiotics like β‐MOS and FOS can serve as physical barrier against gastric and bile stress (Casarotti, Todorov, & Penna, ) by imparting a protective effect due to creation of a microenvironment around bacteria and occluding of water around bacterial vicinity by formation of small aggregates (Villegas & Costell, ). de Almeida et al () also showed that buffering capacity, high fat content and dense matrix of Mascarpone‐type cheese provides significant protection to Bifidobacterium animalis subsp.…”
Section: Resultsmentioning
confidence: 99%